Efficacy and Predictive Factors of the Outcome of Extracorporeal Shock Wave Lithotripsy: A Review of One-thousand-nine-hundredninety-seven Patients - ŞEKERCİ, ÇAĞRI AKIN; TANIDIR, YILÖREN (GALENOS YAYINCILIK, 2019)
Objective: The aim of this study was to evaluate the efficacy and safety of extracorporeal shock wave lithotripsy (SWL) in a large patient group treated with SWL due to kidney stone. Materials and Methods: Data of 1997 patients, who underwent SWL due to renal stone in the at Ataturk University Medical Faculty Clinic of Urology between 2008 and 2013, were evaluated retrospectively. The effect of age, gender, stone location, size and opacity on SWL success, additional procedure requirement and complication rates were evaluated. Results: Six hundred eighty-six patients were female and 1311 were male. The overall rate of success of SWL was found to be 82.6%. The rate of success of SWL was 82.1% in female patients and 82.9% in male patients (p>0.05). Gender, stone location, stone size and opacity were significant predictive factors for the success of SWL (p<0.05). The complication rate in stones >15 mm was 5.8% (p<0.05). Age, gender, stone size, stone location and stone opacity were not predictive factors for additional treatment after SWL (p>0.05). Conclusion: Although SWL is less preferred today with the increase of endourological interventions, it remains an effective treatment method in appropriate patients.
Keywords: Extracorporeal shock wave lithotripsy; Urinary stone; Complication; RENAL STONES; SUCCESS; CALCULI; SIZE; ESWL